STUDI KASUS PERAN STRATEGI EVENT TOURISM FESTIVAL LAMPION WAISAK DALAM MENINGKATKAN DAYA TARIK WISATA RELIGI - Anastasia Landasan; Kris Cahyani Ermawati; Titik Akiriningsih (Universitas Pendidikan Ganesha, 2026)
The Vesak Lantern Festival in the Borobudur Temple area, Magelang, has become a premier tourism event representing an international-scale cultural and religious tourism phenomenon in Indonesia. This study aims to: 1) analyze the role of the Vesak Lantern Festival as a tourism event; 2) examine its management strategies; and 3) comprehensively analyze internal and external factors using a SWOT approach. The study employs a qualitative approach, utilizing primary data obtained through interviews, observations, and documentation involving five key informants. The findings indicate that the festival's management remains oriented toward the conduct of religious rituals; funding is borne entirely by WALUBI without budgetary contributions from relevant ministries, and coordination among stakeholders lacks proportionality. Based on the SWOT analysis, a strategy combining the mitigation of weaknesses and threats—through the establishment of a collaborative governance framework with clearly defined responsibilities—was identified as the priority strategy. Conceptually, this study contributes the insight that management weaknesses in religious tourism events stem from the organizers' dual orientation: balancing the preservation of ritual essence with the professional development of tourism potential.